GE_GERICHTE C/29276/2006 vom 19. Juni 2009 - GE Cour de justice (2009)
; PARTAGE SUCCESSORAL ; RAPPORT SUCCESSORAL ; PRINCIPE DE LA BONNE FOI | CC.8. CC.527. CC.533. CC.602. CC.604. CC.626. CC.634. CO.18. CO.115. CO.239. LPC.399